Education strategy for farmers in Kamanasa to controlling the population of golden snails (Pomacea canaliculated L.) - Blasius Atini (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2022)
The high population of golden snails is a pest of rice for farmers in Kamanasa. Proper education is needed so the farming community can solve this golden snail pest problem independently and sustainably. This study aims to analyze the population density of golden snails in the Malacca Regency Kamanasa rice field area, determine the environmental factors that influence it, and analyze appropriate educational strategies for farming communities. The method used to record the population density of golden snails is a survey method with field observation points determined by purposive sampling. At the same time, the determination of educational strategies is carried out by studying literature. The population density data were analyzed using the population density formula by Odum and Barrett. Based on the research data, the population density of golden snails at observation points I, II, III, IV, and V shows that the density of golden snails in the rice fields of Kamanasa, Malacca Regency is relatively high. Direct learning is the most suitable educational method because people with different cognitive backgrounds can more easily understand concepts through direct interaction in the field. In addition, guidelines written in popular languages are needed so that the community can independently sustainably manage the golden snail.Abstrak Populasi keong emas yang tinggi menjadi hama padi bagi petani di Kamanasa. Edukasi yang tepat diperlukan agar masyarakat tani dapat menyelesaikan masalah hama keong emas ini secara mandiri dan berkelanjutan. Penelitian ini bertujuan untuk menganalisis kepadatan populasi keong emas di areal persawahan Kamanasa di Kabupaten Malaka, mengetahui faktor-faktor lingkungan yang mempengaruhi, dan menganalisis strategi pendidikan yang tepat untuk masyarakat tani. Metode yang digunakan dalam mendata kepadatan populasi keong emas adalah metode survei dengan titik pengamatan lapangan ditentukan secara purposive (Porpusive sampling method), sedangkan penentuan strategi pendidikan dilakukan dengan studi literatur. Data kepadatan populasi keong emas dianalisis menggunakan rumus kepadatan populasi menurut Odum dan Barrett. Berdasarkan data hasil penelitian kepadatan populasi keong emas pada titik pengamatan I, II, III, IV, dan V menunjukan tingkat kepadatan keong emas di areal persawahan Kamanasa Kabupaten Malaka tergolong tinggi. Direct learning (pembelajaran langsung) merupakan metode pendidikan yang paling cocok karena masyarakat dengan latar belakang kognitif yang berbeda dapat lebih mudah memahami konsep melalui interaksi langsung di lapangan. Selain itu, diperlukan pedoman yang ditulis dengan bahasa populer, sehingga masyarakat secara mandiri dapat melakukan penanggulangan keong emas secara berkelanjutan.